Proceedings of the 20th IEEE/ACM International Conference on Automated Software Engineering 2005
DOI: 10.1145/1101908.1101970
|View full text |Cite
|
Sign up to set email alerts
|

Determining the cost-quality trade-off for automated software traceability

Abstract: Major software development standards mandate the establishment of trace links among software artifacts such as requirements, architectural elements, or source code without explicitly stating the required level of detail of these links. However, the level of detail vastly affects the cost and quality of trace link generation and important applications of trace analysis such as conflict analysis, consistency checking, or change impact analysis. In this paper, we explore these cost-quality trade-offs with three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Gotel [13] found that traceability failures primarily happened because of a breakdown of communication between developers, lack of time in the schedule, lack of tool support, and a perception from the product team that the effort required to maintain traceability was excessive. By picking the right implementation strategy for the product team, the cost of implementation versus the benefit of effective traceability can be optimized [9].…”
Section: Cost Of Traceabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Gotel [13] found that traceability failures primarily happened because of a breakdown of communication between developers, lack of time in the schedule, lack of tool support, and a perception from the product team that the effort required to maintain traceability was excessive. By picking the right implementation strategy for the product team, the cost of implementation versus the benefit of effective traceability can be optimized [9].…”
Section: Cost Of Traceabilitymentioning
confidence: 99%
“…If properly implemented, traceability can provide significant benefits. However, its cost can also be significant [9,19]. Therefore a strategy for its implementation must be carefully defined by examining and correlating the set of business, project, product, and technology factors.…”
Section: Selecting a Traceability Strategymentioning
confidence: 99%
“…Spanoudakis et al [17] discuss rule-based traceability of UML models and code. Egyed et al [8] discuss value-based traceability. Hayes et al [10] discuss the use of feedback as well as introduce measures for evaluating traceability methods.…”
Section: Traceability Using Static Datamentioning
confidence: 99%
“…Consequently, value considerations are fundamental to motivate sustainable systematic requirements tracing activities [1]. Initial case studies and value-based software engineering analyses on systematic tracing have provided evidence on options to save considerable parts of tracing costs without sacrificing substantial benefits [7][8] [12].…”
Section: Requirements Traceability Modelsmentioning
confidence: 99%